Impact of educational programmes on the health and dietary practices of the wokers of sewage fram in Thiruvananthapuram Corporation - Razeena K A (Department of Home Science, College of Agriculture, 2000)
A study entitled the' Impact of educational programmes on the health and dietary practices of the workers of sewage farm in Thiruvananthapuram Corporation' was conducted to evaluated the impact of educational programmes on the knowledge and adoption of health and dietary practices by the workers of sewage farm in Thiruvananthapuram and also to find out the comparative effectiveness of the selected teaching methods.